MONEY LAUNDERING CRIME - Abdullah Jalil (Program Pascasarjana UIN Sumatera Utara Medan, 2020)
Money laundering is a complex crime that exploits the financial system to disguise the origins of criminal assets. This study aims to analyze the law enforcement mechanisms for money laundering in Indonesia based on Law Number 8 of 2010. The main focus of the study is to review the strategic roles of the Financial Transaction Reports and Analysis Center (PPATK), the Police, and the Prosecutor's Office in the law enforcement chain. Using normative legal research methods, the study results indicate that the effectiveness of money laundering eradication depends on a follow-the-money approach. The PPATK functions as financial intelligence, the Police as the primary investigator, and the Prosecutor's Office as both prosecutor and asset executor. Synergy between these three institutions is crucial to ensuring maximum state asset recovery.